2017
DOI: 10.26719/2017.23.9.598
|View full text |Cite
|
Sign up to set email alerts
|

Third Study on WHO MPOWER Tobacco Control Scores in Eastern Mediterranean countries 2011-2015

Abstract: This study was conducted to quantify the implementation of the MPOWER policies and to assess any possible changes across Eastern Mediterranean Region (EMR) countries. In this comparative cross-sectional study based on 10 categories mentioned in MPOWER report 2015 a checklist was designed. Seven questions were scored from 0-4 and three from 0-3. The 22 EMR countries were ranked and compared by their total score on a scale of 0-37. The highest scores were achieved by the Islmaic Republic of Iran and Egypt. Pakis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…One of the reasons for the inexpensiveness of WTS in Iran is low tax on tobacco products. Comparison of the Eastern Mediterranean countries respecting tobacco control programs revealed that Iran obtained the highest score for the MPOWER six policies on tobacco control; nonetheless, Iran has not completely been successful in enforcing the smokeless environment law and imposing tax on tobacco products (43). In line with our findings, a study reported that the low price and the easy accessibility of WTS significantly contribute to its high prevalence (34).…”
Section: Discussionsupporting
confidence: 82%
“…One of the reasons for the inexpensiveness of WTS in Iran is low tax on tobacco products. Comparison of the Eastern Mediterranean countries respecting tobacco control programs revealed that Iran obtained the highest score for the MPOWER six policies on tobacco control; nonetheless, Iran has not completely been successful in enforcing the smokeless environment law and imposing tax on tobacco products (43). In line with our findings, a study reported that the low price and the easy accessibility of WTS significantly contribute to its high prevalence (34).…”
Section: Discussionsupporting
confidence: 82%
“…The scores of Afghanistan, Bahrain, Djibouti, Iraq, Jordan, Morocco, Oman, Qatar, Somalia, Syrian Arab Republic and United Arab Emirates also all increased from 2015 to 2017. More tobacco control programmes have recently been introduced in the EMR (20,21), but they need more time for their effectiveness to be felt.…”
Section: Discussionmentioning
confidence: 99%
“…The recent global epidemic of water-pipe is attributed to various factors such as social acceptability and the lack of water-pipe specific regulations [ 30 ]. Although the Islamic Republic of Iran received the highest score in the World Health Organization MPOWER tobacco control program among countries in the Eastern Mediterranean Regional Office, the enforcement has focused on cigarette smoking [ 31 ], while measures such as monitoring water-pipe use and raising taxation on water-pipe are still in progress.…”
Section: Discussionmentioning
confidence: 99%